Telemedicine in Oncology: Delivering on an Overdue Promise in the COVID-19 Era - West, Howard (Jack) (Frontiers in Oncology, 2020)
Telemedicine has historically been underutilized in medicine broadly, and specifically in oncology, despite the general availability of the needed infrastructure to offer it as a platform for remote care. The COVID-19 pandemic posed new risks of infection exposure and potentially life-threatening complications, particularly in patients with cancer, created a new setting for cancer care ideally suited for the rapid roll-out of telemedicine for patients with cancer who need regular follow up but in whom live visits may not be critical. In the months since the upheaval of our health care system and wider society in the United States, as well as other countries, our early experience with telemedicine has demonstrated the feasibility of telemedicine for a subset of patients with cancer, facilitated by a removal of regulatory hurdles and payment parity, at least temporarily. At the same time, however, many patients still need to return to the clinic for routine infusions of anti-cancer therapy that obviate much of the value of remote clinic visits, and many patients remain limited by access to hardware, fast and reliable internet, and technical expertise. While we need to address these shortcomings and ensure training of health care professionals in “webside manner” with patients, as well as to work to develop ways to incorporate remote care in the conduct of clinical trials, telemedicine is poised to emerge not merely as an interim solution to a transient challenge but as a valuable tool ideally suited to deliver cancer care efficiently for a subset of patients well suited to adopt this platform.